BRAIN DEATH IN ISLAMIC ETHICO‐LEGAL DELIBERATION: CHALLENGES FOR APPLIED ISLAMIC BIOETHICS. (13th December 2011) - PADELA, AASIM I.; AROZULLAH, AHSAN; MOOSA, EBRAHIM
ABSTRACT Since the 1980s, Islamic scholars and medical experts have used the tools of Islamic law to formulate ethico‐legal opinions on brain death. These assessments have varied in their determinations and remain controversial. Some juridical councils such as the Organization of Islamic Conferences' Islamic Fiqh Academy (OIC‐IFA) equate brain death with cardiopulmonary death, while others such as the Islamic Organization of Medical Sciences (IOMS) analogize brain death to an intermediate state between life and death. Still other councils have repudiated the notion entirely. Similarly, the ethico‐legal assessments are not uniform in their acceptance of brain‐stem or whole‐brain criteria for death, and consequently their conceptualizations of, brain death. Within the medical literature, and in the statements of Muslim medical professional societies, brain death has been viewed as sanctioned by Islamic law with experts citing the aforementioned rulings. Furthermore, health policies around organ transplantation and end‐of‐life care within the Muslim world have been crafted with consideration of these representative religious determinations made by transnational, legally‐inclusive, and multidisciplinary councils. The determinations of these councils also have bearing upon Muslim clinicians and patients who encounter the challenges of brain death at the bedside. For those searching for 'Islamically‐sanctioned' responses that can inform their practice, both the OIC‐IFA and IOMS verdicts have palpable gaps in their assessments and remain clinically ambiguous. In this paper we analyze these verdicts from the perspective of applied Islamic bioethics and raise several questions that, if answered by future juridical councils, will better meet the needs of clinicians and bioethicists.